NAVIGATING NEW FRONTIERS: A CRITICAL REVIEW OF NURSES’ EXPANDING ROLES BEYOND TRADITIONAL PATIENT CARE - Salem Mohammed Al Khorem; Majed Mahdi Saleh Al Ghaber; Mabkhwt Mohammed Mabkhwt Alkhzayam; Hussain Hamad Ali Alkhuraym; Salem Hamad Hassan Alyami; Ali Salem Saleh Alkhreem (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The evolving landscape of healthcare has precipitated a significant expansion in the roles of nurses, extending far beyond traditional patient care. This critical review delves into the multifaceted roles that nurses now embody, including as nurse practitioners with increased autonomy, leaders in healthcare administration, public health advocates, educators, researchers, and policy influencers. Against the backdrop of a historical perspective, this article examines the catalysts driving the evolution of nursing roles, underscored by global health challenges and the shifting needs of patient care. It highlights the inherent challenges and opportunities that accompany these expanded roles, such as regulatory hurdles, the necessity for advanced education, and the dynamics of interprofessional collaboration. Through an analysis of real-world case studies, the article showcases the tangible impacts of these expanded roles on healthcare outcomes and systems. Furthermore, it projects into the future of nursing, considering the implications of technological advancements and the preparation required for upcoming generations of nurses. This review underscores the critical importance of supporting the evolving roles of nurses to harness their full potential in advancing healthcare.